Reverse generative learning: Intergenerational learning for global readiness in higher education - Liang, Wenrui; Shamshudeen , Rosya Izyanie; Md Syed, Md Azalanshah; Hui, Shen (Journal of International Students, 2025)
This paper examines the impact of senior influencers on Douyin and their role in shaping the educational perceptions of postgraduate students in mainland China. The paper comprises 23 semistructured interviews with students in Guangdong, exploring three themes: algorithm-driven intergenerational identity fluidity, the decentralization of knowledge authority on social platforms, and emotional algorithmizing and reflective agency. The findings include the influence of senior influencers, who provide knowledge input and participate in co-creation with students, thereby causing cognitive and emotional shifts. This paper contributes to the discourse on how technological and policy-informed environments facilitate transformative and situation-specific learning, specifically examining intergenerational interactions on social platforms. Although the paper involves local interviews, they correlate with global student mobility in terms of guidance by the ‘elder,’ which is influenced by platforms, contributing to the determination of risk factors, destinations, and time, ultimately leading to local practical applications in global higher education.